Neonatal Riga-Fede disease: A systematic review of 84 cases collected over 120 years - Alagar Thirumalai , Rangapriya; Raveenthiran, V (Journal of Neonatal Surgery, 2024)
Background: Traumatic ulceration of the tongue due to congenital teeth is known as Riga-Fede disease (RFD). The literature on RFD consists largely of anecdotal case reports, thereby lacking valid clinical recommendations. While managing a newborn with RFD complicated by Ludwig’s angina, this knowledge gap was recognized. Therefore, this systematic review was conducted to gain insight into the optimal management and the possible complications of RFD. Methods: A literature search was conducted using PubMed, Google Scholar, and Science Direct, supplemented with African Journals Online, Indmed, and manual searches. Papers published between 1900 and July 2023 in any language were retrieved. Neonates with natal or neonatal teeth and ulceration of the oral mucosa were included. Papers with incomplete data and review articles were excluded. Results: A total of 84 newborns with RFD from 62 published reports (including the case reported herein) were analyzed. Most of the reports were from the Indian subcontinent, and the frequency of reporting has increased since the year 2000. Tongue ulceration in all cases was due to mandibular incisors. There was no significant difference in the median duration of healing between the tooth extraction group (14 days) and the conservative management group (18 days). There was only a very weak positive correlation between the duration of symptoms and healing time, which was statistically insignificant. Conclusion: Healing of mucosal ulcers in RFD is often protracted and does not appear to be influenced by the duration of symptoms or by the modality of treatment. Extraction of the offending teeth is more common (75% of cases) than conservative management, such as grinding (ameloplasty) or resin capping of teeth. RFD is mostly a benign disorder; however, serious complications such as meningitis, Ludwig’s angina, and soft tissue abscesses can rarely occur with Staphylococcus aureus infections.